948 THE DEVELOPMENT OF A DYSPHAGIA CUP TO IMPROVE WATER INTAKE AND REDUCE CAREGIVER BURDEN IN CHANGI GENERAL HOSPITAL (CGH). (14th June 2022) - Lim, S C; Arroyo, S P; Li, F; Lee, Y Q; Chew, X J; Sinatamby, S
Abstract:  : At any one time, >60% of the beds in the 1, 000 bedded CGH is occupied by an elderly >65. Ensuring adequate water intake among the elderly patients is a challenge. Hence, 90% of our elderly inpatients in the acute wards did not consume the recommended daily allowance of fluid. Causes for poor water consumption included dysphagia requiring thickened fluids, manpower reasons, patient and environmental factors. The Geriatrician led a team to explore, designed and developed a dysphagia cup to improve fluid intake for the elderly inpatients, with input from nursing, occupational and speech therapists. The plan-do-study-act methodology was employed in this study. Training was provided to nursing staff and caregivers prior to issuing the cups. Results: The cup improves availability of water for the patients, encourages autonomy so the patients may drink independently without aspirating, reduces caregiver burden while thickening prior to serving fluids and improves patient care. The improved water consumption reduces adverse outcomes associated with dehydration such as delirium, constipation and long length of stay. Results showed improvement in water consumption among 75% of the patients, with 62% increase in amount of fluid consumption. 83% of patients were able to drink independently with >90% caregiver (nurses and family) satisfaction. The cups saved nursing time significantly, projected to save 14 full time nurses a year and 67% improvement in nursing productivity, for CGH. Conclusion: Encouraging the elderly to drink is labour intensive and time consuming, especially for patients with dysphagia. Time saving was proven for thickening fluids and since patients drink independently, time was saved for assisting/supervising patients while drinking. Since the cup has measuring gauge, it was faster to thicken fluids. The cup holds enough fluids for several serving, the caregiver need not prepare to thicken fluids prior to every serving.